Apprenticeship training in Germany - still a future-oriented model for recruiting skilled workers? - Walden, Günter [Verfasser]; Troltsch, Klaus [Verfasser] (My University, 2011)
"The apprenticeship training system in Germany, where training takes place in both private companies and vocational schools, has traditionally played an outstanding role in the development of young skilled workers. However, particularly since the start of the new millennium, the chances of smooth transition from secondary school to an apprenticeship have worsened. As a consequence, there has been an intensive political and academic discussion about whether the German dual vocational training system is still in keeping with the times. In the following, we will examine whether apprenticeship training can continue to be the primary model for recruiting skilled workers. It will be shown that the insufficient number of apprenticeship places in recent years is less the result of any supposed obsolescence of this training system than of the close link between the apprenticeship system and the employment system." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; G 1.3.1.1 Ausbildungsstellenmarkt; G 1.3.2.2.1 Erste Schwelle, in Ausbildung; G 1.2.3.2 Anforderungen & Bedarfe; Duales System; Berufseinmündung; Erste Schwelle; Fachkräftebedarf; Personalgewinnung; Beziehung Bildungssystem Beschäftigungssystem; Demografischer Wandel; Ausbildungsstellenmarkt; Ausbildungsplatzangebot; Ausbildungsplatznachfrage; Quantitative Angaben